Fabrication of icephobic aluminium surfaces by atmospheric plasma jet polymerisation. (4th May 2019) - Jafari, Reza; Momen, Gelareh; Eslami, Esmaeil
ABSTRACT: Atmospheric plasma treatment followed by a plasma polymerisation coating produced an aluminium surface having high water repellency and icephobicity. We varied the plasma parameters and the amount of hexamethyldisiloxane precursor to optimise surface hydrophobicity. The static contact and sliding angles of the surface reached 163° and <1°, respectively. Furthermore, the prepared surfaces remained superhydrophobic after seven days of immersion in acid–base media as well as after five icing/de-icing cycles.